The Effect Of Profitability, Company Size, Funding Decisions And Investment Decisions On Firm Value (Study Of Property And Real Estate Sector Companies Listed On The Indonesia Stock Exchange For The Period 2021-2023) - Amantra, Muhammad Vemas; Hadli, Hadli; Ikraam, Ikraam (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the influence of Profitability, Firm Size, Financing Decisions, and Investment Decisions on Firm Value in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The approach used is a quantitative method with secondary data obtained from the annual financial reports of 93 companies selected through purposive sampling based on specific criteria. The analysis technique used is panel data regression with the assistance of SPSS 25 software to test the relationship between variables. The results of the study indicate that Profitability and Investment Decisions have a positive and significant influence on Firm Value. Conversely, the variables of Company Size and Financing Decisions did not show a significant effect on Company Value. These findings imply that increasing profitability and making appropriate investment decisions can be key strategies in increasing company value in the property and real estate sector.